EFEKTIVITAS FOCUS GROUP DISCUSSION UNTUK MENGURANGI STRES PADA SISWA SMA YANG AKAN MENGHADAPI UJIAN AKHIR NASIONAL - Aprilia, Dina (Faculty of Ushuluddin and Humanities, 2016)
This research is aimed to find the effectivity of Focus Group Discussion (FGD) to decrease the feeling stress for senior high school students (SMA) who will face the national final examination (UAN). Stress on SMA students is a circumstance which gets negative assessment. It intimidates and pushes the students, in this case is UAN would appear a reaction such as emotional disorder, cognition, physiology and behavior disorder of SMA students. This research concerned 21 SMA students in grade XII, who had high stress level in facing UAN. The subjects were divided into two groups. First group was the experiment group (include 11 students) and it was the group who got the FGD treatment. The second group was control group (include 10 students) and this group didnât get the FGD treatment. Collecting data was done by using Stress Scale in facing UAN. It was given (a) before FGD (pre-test) and (b) after FGD (post-test). The hypothesis is examined by using difference examination (t-test) by comparing mean pre-test and post-test. The result showed that there was a significant influence to decrease the stress in SMA students who were in experiment group (t = 6,540, p < 0,01) after they got FGD treatment. Experiment group had decreased the stress score to face UAN (Mean=7,476).